Morphological and Molecular Variability of Rhizoctonia solani Isolates Causing Banded Leaf and Sheath Blight in Maize - Madhavi, M.; Reddy, P. Narayan; Reddy, R. Ranga; Reddy, S. Sokka (International Journal of Bio-resource and Stress Management, 2015)
Twenty seven isolates of Rhizoctonia solani causing Banded Leaf and Sheath Blight in maize were collected from different maize varieties and one from rice grown in various regions of Telengana State, India for easy breeding task. The isolates were analysed for their morphological and genetic characterization. The hyphal width varied from 5.00 (RS2, RS20) to 7.97 μm (RS10) of rice isolate (7.34 μm). The isolates RS7, RS 8, RS9 (Karimnagar), RS10, RS11, RS12 (Khammam) RS16 (Krishna) and RS26 (Kurnool) and one rice isolate RS28 produced barrel shaped monilioid cells. The clamp connection was present only in RS1 isolate from Pragnyapur mandal of Medak district. The three isolates RS16, RS17, RS18 from Krishna district and rice isolate RS28 recorded maximum colony growth of 90.00 mm within 48 h of incubation. The colour of most isolates varied from light grey to brown while the rice isolate showed a typical yellowish brown shade. The sclerotial number per 5.00 mm culture disc of test isolates ranged from between (7.00) to (17.67). Their size varied between 0.21 μm (RS 24) and 1.57 μm (RS11). The rice isolate RS28 recorded highest (19.00) sclerotial count compared to that of maize isolates. Sclerotial colour in all isolates except for RS 24 was yellowish brown to dark reddish brown whereas the rice isolate was dark yellowish brown. Molecular characterization of the test isolates using RAPD markers with UPGMA exhibited two major clusters with 66 to 90% genetic similarity.